2018
DOI: 10.1177/1359105318803708
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal associations among grandparent–grandchild cohesion, cultural beliefs about adversity, and depression in Chinese rural left-behind children

Abstract: This study examined the effects of grandparent–grandchild cohesion on the cross-lagged associations between depression and cultural beliefs about adversity in a sample of 625 rural left-behind children in China. Grandparent–grandchild cohesion was concurrently and longitudinally associated with children’s depression and cultural beliefs about adversity. Cultural beliefs about adversity mediated the associations between grandparent–grandchild cohesion and children’s depression, while depression mediated the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…This was consistent with the study of Zhang and colleagues [64]. The explanation for this could be that Chinese left-behind children, in particular female children, tend to acquire positive cultural values in the face of adversity [65]. According to the findings, Chinese female children who adhere to positive cultural views about adversity might develop hope and optimism in the face of adversity, such as parental absence.…”
Section: Discussionsupporting
confidence: 91%
“…This was consistent with the study of Zhang and colleagues [64]. The explanation for this could be that Chinese left-behind children, in particular female children, tend to acquire positive cultural values in the face of adversity [65]. According to the findings, Chinese female children who adhere to positive cultural views about adversity might develop hope and optimism in the face of adversity, such as parental absence.…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to our expectation, however, this study found no significant differences in peer relationship profiles between adolescents with two migrating parents and adolescents with non-migrating parents. This finding may be related to the fact that grandparents from both-parent-migrant families play a parent-like role by providing immediate emotional support, guidance, supervision, and coping skills for their left-behind grandchildren (Li et al, 2018). Another possible explanation is that adolescents from both-parent-migrant families may be more eager to interact with their peers to acquire a sense of belonging and security in their peer relationships, which may compensate for parents' emotional unavailability.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, those children of parents who migrate to urban areas become 'left-behind children' (Duan and Zhou, 2005). However, the left-behind experience has a negative impact on the physical and mental development of individuals (Li et al, 2018). For instance, individuals with left-behind experience cannot get timely psychological counseling and emotional support due to the long-term absence of their parents (Wang et al, 2019), thus developing maladaptive coping strategies and NSSI is one of them (Guerreiro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%